Christian Citizens and the Christianity with Chinese Characteristics - LI, Xiangping (Journal of Research for Christianity in China (JRCC), 2025)
The unique tension between Christian internal fellowship and external environment, to a certain extent, making the rapid development of Christianity in contemporary Chinese society. But the extension of this tension also led to the concept that institutional religions are not conducive to national identity，thus also constitute the problem of the indigenization of contemporary Christianity. There is a lack of public interaction space in China’s religious belief systems, therefore need to construct a public faith way. Christian background, such as identity, profession and education, combined with their faith way, and were integrated into the faith practice. So we should use citizenship to express and regulate personal religious beliefs, let personal faith becomes the consensus and identity of a social level. The core issue of the Christian indigenization is the integration between the citizen of the Christian faith and the public identity, the social role transformation of China’s Christianity will happen, when it won the identity of citizens’ faith and the way of their faith.
Keywords: Christianity, way of citizens’ faith, social identity